Management Control System in Practices: A Case Study of Koteshwor Multiple Campus - Budhathoki, Dhiraj; Nepal , Binod (KMC Research Journal, 2024)
The study examines the role of Management Control Systems (MCS) in educational institutions, focusing on Koteshwor Multiple Campus, highlighting challenges such as inadequate financial oversight, limited information system integration, and ineffective academic quality assurance. Through qualitative case study research, this study aims to evaluate the impact of existing MCS within KMC, exploring its practices, consequences, and potential areas for improvement.The study highlights KMC's MCS components, including control environment, recruitment, budgetary controls, performance monitoring, risk assessment, and communication systems. It emphasizes the importance of comprehensive control environments and standardized procedures.Based on the identified gaps in existing MCS, the study recommends ways for KMC to improve its control systems, such as creating structured control environments, implementing standardized recruitment procedures, establishing dedicated budgetary control mechanisms, expanding performance monitoring efforts, and strengthening communication channels. These recommendations seek to increase openness, accountability, and overall institutional performance, eventually supporting KMC's objective of academic excellence and organizational sustainability.